Mass Producing Innovation: A Case Investigation on Why Accelerators Might Not Be a Paradox - Andrew Barnes (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
There are a growing number of accelerator programmes designed to start and support innovative startup businesses. Many accelerators are increasing the size of their intakes, with some programmes now launching over 200 new companies per year. On first inspection the large numbers and consistent approach taken to accelerating the participating companies appears to be in conflict with producing innovative and disruptive companies. This paper uses Y Combinator as a single case study to investigate whether increasing the number of companies within a batch has resulted in longer or shorter timeframes for companies to achieve an exit (through acquisition or initial public offering). The paper finds that the timeframe for achieving an exit for Y Combinator companies is reducing, even while batch size has sharply increased. There is no statistically significant correlation between the cohort size and the initial money raised during the programme. Keyword : Accelerators, Startups, Innovation